Evaluation of the effectiveness of different diets for weight loss (Research, Society and Development, 2024)
Obesity is a rapidly spreading epidemic. Having become a public health problem. As a result, several diets aimed at weight loss have emerged. Therefore, the objective of this study was to study the different diets for weight loss: low carb, intermittent fasting and ketogenic. The present study was a bibliographical review of the last 10 years using health descriptors in Portuguese and English, and also scientific journals widely known for public health. Ketogenic diets are a safe option for achieving considerable weight loss, but they must be part of a strategy under full medical supervision. It was found that intermittent fasting can improve metabolic markers related to metabolic syndrome, but there are uncertainties about its effectiveness, long-term effects and safety, which is why the use of individualized approaches is necessary. And although the low carb diet is effective for reducing body weight, triglycerides, glycemic control and increasing HDL levels if carried out correctly. But the conventional balanced diet remains the safest way of treatment. Therefore, it is important that before choosing one of these diets, the individual first undergoes a nutritional assessment to understand which of these diets is most suitable for their case.